International investors, contagion and the Russian crisis - Alexei Medvedev (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
The paper provides detailed empirical assessment of the role of non-residents in the development of Russian financial crisis in 1997-1998.It is established that non-residents behaved differently during the period of crisis and significantly contributed to the collapse of the state bonds market.In particular, we found that sharp downturn in May 1998 was caused by contagious selling on the part of foreign investors following Indonesian crisis.At the same time, we question the common view that non-residents were largely responsible for market pressures at the initial stage of the crisis.In this paper we go a little beyond the discussion of Russian crisis and propose alternative explanation of contagious outflow of foreign capital.We combine CAPM and findings of Forbes and Rigobon (2001) to show that international portfolio investors are more sensitive to pure external shocks and less sensitive to pure domestic ones.
URN:NBN:fi:bof-201408072087
Keywords: 330